O impacto da obesidade na síndrome respiratória aguda grave causada pelo novo coronavírus (SARS-COV-2) - Susin, Karine Sabrina Bonamigo (2022)
COVID-19 is an infection caused by a new type of Coronavirus, which was identified in China at the end of 2019. In late March the World Health Organization declared a pandemic and by January 2022, there were more than 336 million people infected. Clinical manifestations of COVID-19 include asymptomatic carrier status, acute respiratory disease, and pneumonia. Most infected people will have mild to moderate symptoms, but approximately 5% will require intensive treatment. Laboratory diagnosis of the disease is performed through real-time RT-PCR and partial or total sequencing of the viral genome, collected through Nasopharynx Swab or Oropharynx. According to the Brazilian Ministry of Health, adults over 60 years of age with cardiovascular diseases, diabetes or obesity may be at higher risk for complications. The primary aim of was to verify if mortality among patients with obesity hospitalized in intensive care units (ICU) por COVID-19 and severe acute respiratory syndrome (RS) was higher than among non-obese. The secondary aim was to verify if obesity is associated with the need for invasive mechanical ventilation, renal replacement therapy and tracheostomy. A Historical Cohort study was conducted between March 2020 and January 2021. Patients with a confirmed diagnosis of Covid-19 and who were hospitalized in ICUs at São Lucas Hospital at PUC-RS and Ernesto Dornelles Hospital in the city of Porto Alegre were included in the study. Data from the medical records of the selected patients were reviewed. Patients with and without obesity were compared using logistic regression to estimate the risk of mechanical ventilation, renal replacement therapy, tracheostomy, and death. Of the 257 patients with COVID-19 and SRAG hospitalized in the ICU, 42% were obese. The mean age of obese patients was 12 years younger than that of non-obese. We found an association with age ≥ 70 years with mortality (OR 6.38 95%CI 3.48-11.69). Crude analysis showed reduced risk of death for obese patients (OR 0.41 95%CI 0.24-0.68). After adjusting for age, sex and comorbidities, obesity was not associated with mortality, mechanical ventilation, renal replacement therapy, and tracheostomy. In conclusion, we did not find in a higher mortality among obese patients admitted to a intensive care unit with COVID-19 and SRAG when compared to non-obese patients. In our study, obesity was not associated with invasive mechanical ventilation, renal replacement therapy and tracheostomy.